Advanced methods of LGD estimation - Egorova, Yulia; Witzany, Jiří, 1966-; Pýcha, Mikuláš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This Thesis has the main aim to consider the most important Basel requirements and parameters and methods of estimation of one of them – Loss Given Default. In Internal Rating Based Approach (IRB) frameworks banks are allowed to assess credit risk using their own models. Precise evaluation of risk parameters is important for banks to calculate regulatory capital to be able to absorb potential losses. Several methods of LGD estimation were investigated in this work in order to compare their performance. Paper briefly describes key Basel risk parameters and explains main approaches to estimation of parameters provided by Basel Accord. Investigated models are considered from the theoretical point of view and applied on the real loan data. Results show that logistic regression and Beta regression models have better fit than other valuated models. Comparison is provided using R-squared measure.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses